Is open access affordable? Why current models do not work and why we need internet‐era transformation of scholarly communications. Issue 1 (24th January 2019) - Green, Toby
Abstract : Progress to open access (OA) has stalled, with perhaps 20% of new papers 'born‐free', and half of all versions of record pay‐walled; why? In this paper, I review the last 12 months: librarians showing muscle in negotiations, publishers' Read and Publish deals, and funders determined to force change with initiatives like Plan S. I conclude that these efforts will not work. For example, flipping to supply‐side business models, such as article processing charges, simply flips the pay‐wall to a 'play‐wall' to the disadvantage of authors without financial support. I argue that the focus on OA makes us miss the bigger problem: today's scholarly communications is unaffordable with today's budgets. OA is not the problem, the publishing process is the problem. To solve it, I propose using the principles of digital transformation to reinvent publishing as a two‐step process where articles are published first as preprints, and then, journal editors invite authors to submit only papers that 'succeed' to peer review. This would reduce costs significantly, opening a sustainable pathway for scholarly publishing and OA. The catalyst for this change is for the reputation economy to accept preprints as it does articles in minor journals today.